Strabismus Incidence in a Danish Population-Based Cohort of Children - Torp-Pedersen, Tobias (JAMA Ophthalmol, 2017)
IMPORTANCE: To our knowledge, there have been few population-based studies of strabismus incidence conducted. Our population-based study provides valuable data for health services planning and identifying research needs. OBJECTIVE: To determine the incidence and age distribution of strabismus, overall and by subtype, among children 7 years or younger. DESIGN, SETTING, AND PARTICIPANTS: This population-based cohort study was conducted with data from 96 842 children enrolled in the Danish National Birth Cohort. MAIN OUTCOMES AND MEASURES: Age-specific incidence and cumulative incidence and median age at the detection of strabismus, overall and by subtype. RESULTS: The study cohort included 96 842 children born between 1996 and 2008 who are predominantly Caucasian and is composed of approximately 30% of births in Denmark, with a boy-girl ratio of 51:49. Overall, 1309 cases of strabismus were identified in the cohort. We found an overall cumulative strabismus incidence of 2.56% (95% CI, 2.42-2.69) at 7 years. The overall incidence was similar among boys and girls. Two hundred sixteen participants (16.5%) (95% CI, 14.5-18.6) had congenital esotropia, 177 (13.5%) (95% CI, 11.7-15.5) had fully accommodative esotropia, 252 (19.3%) (95% CI, 17.1-21.5) had partially accommodative esotropia, and 181 (13.8%) (95% CI, 12.0-15.8) had exotropia. The esotropia:exotropia ratio was 5.4:1 (95% CI, 3.4:1 to 7.5:1). Age-specific incidence curves for congenital esotropia, fully accommodative esotropia, partially accommodative esotropia, and all exotropia revealed interactions between strabismus subtype and age, suggesting that the different subtypes had different age-specific patterns of incidence (P < .001 for all comparisons between pairs of curves). The median age at detection for the 4 subtypes was 0, 32.0, 26.1, and 16.6 months, respectively. CONCLUSIONS AND RELEVANCE: In a national, population-based cohort study, we found a cumulative incidence of strabismus consistent with those reported in smaller European and American cohorts, but a somewhat higher esotropia:exotropia ratio than those that, to our knowledge, are typically reported by English and American studies. Patterns of incidence by age differed for different strabismus subtypes, indicating differences in age at onset and thereby implying differences in the underlying etiology.